Spectrum allocation model for cognitive wireless networks based on the artificial bee colony algorithm - Cesar Hernandez; Jorge Rodriguez; Diego Giral (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Cognitive radio through dynamic spectrum allocation allows an efficient use of the radio-electric spectrum. It is a key subject for the performance of cognitive radio networks. The purpose of the present article is to develop a spectrum allocation model for cognitive wireless networks based on the Artificial Bee Colony algorithm and assess its performance in spectrum occupancy traces obtained from monitoring the spectrum using the energy detection technique. Results show a reduction in the number of spectral handoff with no excessive execution times.